Effect of hemodialysis on the biotransformation of oxo-eicosatetraenoic acids in peripheral tissues - Tong LIU; Gollasch Maik; C. Luft Friedrich; Pan LIN; Jun JI; Yao MENG (Zhongguo Linchuang Yixue)
ObjectiveTo analyze the differences of free and esterified oxo-eicosatetraenoic acids (oxo-ETEs) in blood cells and plasma from arterial and venous blood in hemodialysis (HD) patients. MethodsArterial and venous blood samples from 12 patients with end-stage renal disease (ESRD) before and after HD treatment at Charité – Universitätsmedizin Berlin, Germany, from June to December 2020 were collected. The esterified and free oxo-ETEs derived from arachidonic acid in blood cells and plasma were measured by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). ResultsNeither esterified nor free oxo-ETEs in blood cells displayed significant arteriovenous differences before and after HD. HD predominantly affected the metabolic levels of esterified and free oxo-ETEs in plasma. HD reduced the arteriovenous differences of esterified 12-oxo-ETE, free 15-oxo-ETE, and free 5-oxo-ETE in plasma, while raised the arteriovenous differences of esterified 15-oxo-ETE. ConclusionsThe oxo-ETEs in blood cells are relatively well-stabilized responding to HD treatment, whereas arteriovenous differences of free and esterified oxo-ETEs in plasma are present and active in response to HD treatment, potentially contributing to the cardiovascular disease.